American lobsters (Homarus americanus) not surviving during air transport: evaluation of microbial spoilage - Erica Tirloni (Italian Journal of Food Safety, 2016)
Eighteen American lobsters (Homarus americanus), dead during air transport, were analysed in order to evaluate the microbial population of meat, gills and gut: no specific studies have ever been conducted so far on the microbiological quality of American lobsters’ meats in terms of spoilage microbiota. The meat samples showed very limited total viable counts, in almost all the cases below the level of 6 Log CFU/g, while higher loads were found, as expected, in gut and gills, the most probable source of contamination. These data could justify the possibility to commercialise these notsurviving subjects, without quality concerns for the consumers. Most of the isolates resulted to be clustered with type strains of Pseudoalteromonas spp. (43.1%) and Photobacterium spp. (24.1%), and in particular to species related to the natural marine environment. The distribution of the genera showed a marked inhomogeneity among the samples. The majority of the isolates identified resulted to possess proteolytic (69.3%) and lipolytic ability (75.5%), suggesting their potential spoilage ability. The maintanance of good hygienical practices, especially during the production of ready-to-eat lobsters-based products, and a proper storage could limit the possible replication of these microorganisms.